Neuroarchitecture and Design in Home Office: Guidelines for Projects and Workspace Adaptations - Vizioli Liborio, Flavia Heloisa [UNESP]; Bortoleto, Ludmila Araujo [UNESP]; Inglesis Barcellos, Ekaterina Emmanuil [UNESP]; Botura, Galdenoro [UNESP] (Univ Catolica Colombia, Fac Diseno, 2023)
Home office work has become routine in global society daily life as a result of the pandemic. In the new context, family living and living spaces had to be adapted for online remote activities. Initially positive, this modality was impacted by inadequate ergonomics and environment, and by anxiety and insecurity regarding the objectives and goals to be achieved, affecting physical and mental health, resulting in a consequent decrease in initial satisfaction and productivity fluctuations. Based on research carried out with home office users, this article analyzes the perception of these individuals about the productivity obtained in the adapted spaces. It demonstrates that the view on the constitution of this workplace does not correspond to what the literature recommends as pleasant and productive. As a result of the research, the article presents a way to improve and increase the productivity and health of its users, and proposes guidelines for the development of projects and adaptations of residential environments for home office, based on the concepts of neuroarchitecture, physical ergonomics and cognitive, biophilic design and user experience (UX). The application of the proposed guidelines will make it possible to create a healthy, productive environment suitable for the well-being of those who use it.
Keywords: home office ergonomic design; neuroarchitecture; biophilic design; health at home office; home office productivity